The Value of Reunification in Germany: An Analysis of Changes in Life Satisfaction - Paul Frijters; John P. Haisken-DeNew; Michael A. Shields (Institute for the Study of Labor (IZA), 2002)
We quantify the value of changes in life circumstances in Germany following reunification. To this end, we develop and implement a fixed-effect estimator for ordinal life satisfaction in the German Socio-Economic Panel. We find strong negative effects on life satisfaction from being recently fired, losing a spouse through either death or separation and time spent in hospital, whilst we find strong positive effects from income and marriage. Using a new causal decomposition technique, we find that East Germans experienced a continued improvement in life satisfaction after 1990 to which increased household incomes contributed around 12%. Most of the increase is explained by improved average circumstances, such as public services. For West Germans, we find virtually no change in satisfaction between 1991 and 1999.
Keywords: C23; Z1; I31; C25; 330; Life satisfaction; German reunification; random and fixed-effects; panel models; causal decomposition; Lebensqualität; Lebensstandard; Nationale Einheit; Öffentliche Meinung; Schätzung; Deutschland; Neue Bundesländer; Lebenszufriedenheit